Static & dynamic pelvic floor assessment using MR defecography: a radiological prospective observational study with ideal reporting template - Sanket Vinubhai Davra; Anushka Jain; Anurag Kumar (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Dynamic pelvic floor assessment is essential for diagnosing functional disorders. MR defecography has emerged as a superior imaging technique due to its detailed visualization capabilities during defecation. This prospective observational study over six months evaluated pelvic floor disorders using dynamic MR defecography and correlated findings with clinical evaluations. Results We included 45 adult patients with pelvic floor symptoms, excluding those with contraindications for MRI or inability to complete the procedure. A total of 42 patients completed the study, comprising 24 females (57.1%) and 18 males (42.9%), with a mean age of 63.9 years. Patients underwent clinical assessments, focusing on the bladder, uterus, vagina, rectum, and anus. MR defecography was performed using a 1.5 Tesla MRI machine, capturing static and dynamic phases, with prolapse quantified relative to the pubococcygeal line. Descent of pelvic organs and pelvic floor weakness were measured during rest, strain, squeeze, and defecation. Conclusion The study highlighted MR defecography’s utility in diagnosing pelvic floor disorders, showing high sensitivity and specificity. Despite limitations like higher costs and the need for patient cooperation, MR defecography offers detailed, dynamic images of the pelvic floor, enhancing diagnostic accuracy and guiding effective treatment strategies. This technique significantly advances pelvic floor dysfunction management, contributing to improved patient outcomes.